Asymptomatic migration of ureteral stent to superior vena cava after ultrasound-guided percutaneous nephrolithotomy: An extremely rare case and review of the literature - Amir Hossein Hassani; Hooman Kamran; Javad Kojuri; Helia Bazroodi; Hossein Fatemian; Alireza Rasekhi; Nima Naderi; Saeed Kooshafar; Anahita Dehghani; Abdolreza Haghpanah (Urology Case Reports)
Ureteral stent migration should be considered a rare complication of urologic procedures. We report a 69-year-old woman diagnosed with ureteral stent migration two weeks after undergoing percutaneous nephrolithotomy while she was symptom-free. The stent passed through the heart and extended to the superior vena cava and right brachiocephalic vein. After excluding thrombus formation, the stent was retrieved using an endovascular approach. Stent migration to the superior vena cava while being asymptomatic is extremely rare. Considering this complication is crucial to prevent consequent fatal events. This case report highlights this rare complication of ureteral stent placement and reviews its management.